2019
DOI: 10.1038/s41598-019-38645-0
|View full text |Cite
|
Sign up to set email alerts
|

The Amazon rain forest plant Uncaria tomentosa (cat’s claw) and its specific proanthocyanidin constituents are potent inhibitors and reducers of both brain plaques and tangles

Abstract: Brain aging and Alzheimer’s disease both demonstrate the accumulation of beta-amyloid protein containing “plaques” and tau protein containing “tangles” that contribute to accelerated memory loss and cognitive decline. In the present investigation we identified a specific plant extract and its constituents as a potential alternative natural solution for preventing and reducing both brain “plaques and tangles”. PTI-00703 cat’s claw (Uncaria tomentosa from a specific Peruvian source), a specific and natural plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 99 publications
3
70
0
3
Order By: Relevance
“…This study was performed to identify whether certain components of U. tomentosa extracts have potential therapeutic effects against COVID-19. To this purpose, a database of 26 compounds that have shown prevalence on the herbal therapeutic activity has been generated ( Figure 1) (Aquino et al, 1990(Aquino et al, , 1997Batiha et al, 2020;Keplinger et al, 1998;Kitajima et al, 2000;Lima-Junior et al, 2013;Lock et al, 2016;Montoro et al, 2004;Navarro et al, 2019Pavei et al, 2012;Peñaloza et al, 2015;Snow et al, 2019;Vera-Reyes et al, 2015). Our initial hypothesis is that cat's claw should contain molecules with highest therapeutic profiles against SARS-CoV-2, by disrupting SARS-CoV-2/ACE-2 association or by inhibiting SARS-CoV-2 spike protein.…”
Section: Database Of U Tomentosa Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed to identify whether certain components of U. tomentosa extracts have potential therapeutic effects against COVID-19. To this purpose, a database of 26 compounds that have shown prevalence on the herbal therapeutic activity has been generated ( Figure 1) (Aquino et al, 1990(Aquino et al, , 1997Batiha et al, 2020;Keplinger et al, 1998;Kitajima et al, 2000;Lima-Junior et al, 2013;Lock et al, 2016;Montoro et al, 2004;Navarro et al, 2019Pavei et al, 2012;Peñaloza et al, 2015;Snow et al, 2019;Vera-Reyes et al, 2015). Our initial hypothesis is that cat's claw should contain molecules with highest therapeutic profiles against SARS-CoV-2, by disrupting SARS-CoV-2/ACE-2 association or by inhibiting SARS-CoV-2 spike protein.…”
Section: Database Of U Tomentosa Bioactive Compoundsmentioning
confidence: 99%
“…Bioactive constituents of U. tomentosa extracts include proanthocyanidins [proanthocyanidin B2 (the main component), proanthocyanidin B4, proanthocyanidin C1, an epicatechin trimer, epiafzelechin-4b!8-epicatechin and an epicatechin tetramer] (Batiha et al, 2020;Navarro-Hoyos et al, 2017), oxindole alkaloids (isopteropodine, pteropodine, rhynchophylline, mytraphylline, speciophylline, uncarine F and uncarine E), indole alkaloidal glucosides (cadambine, 3dihydrocadambine and 3-isodihydrocadambine) (Batiha et al, 2020;Kura s et al, 2009;Laus et al, 1997;Lima-Junior et al, 2013;Lock et al, 2016;Navarro et al, 2019Snow et al, 2019), quinovic acid glycosides (Pavei et al, 2012), tannins (Ostrakhovich et al, 1997), polyphenols, catechins, beta sitosterol (Aquino et al, 1997;Navarro et al, 2019) and proteins (Lenzi et al, 2013), which individually or synergistically contribute to their therapeutic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Uncaria tomentosa has documented neuroprotective effects in preclinical studies (110), and preliminary human studies have shown improved quality of life in individuals with cancer (111), enhanced DNA repair (112), and symptom improvement in individuals with rheumatoid arthritis (113) and osteoarthritis (114). The potential antimicrobial effects of Uncaria tomentosa have not been widely evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Uncaria tomentosa is an important medicinal plant from South and Central America and has been shown to have neuroprotective effects in preclinical studies (152) (and in preliminary human studies has been shown to improve quality of life in individuals with cancer (153), enhanced DNA repair (154), and symptom improvement in individuals with rheumatoid arthritis (155) and osteoarthritis (156). The potential antimicrobial effects of Uncaria tomentosa have not been widely evaluated.…”
Section: Discussionmentioning
confidence: 99%